Treatment of Cerebral Cavernous Malformations Presenting With Seizures: A Systematic Review and Meta-Analysis - Gao, Xiangyu; Yue, Kangyi; Sun, Jidong; Cao, Yuan; Zhao, Boyan; Zhang, Haofuzi; Dai, Shuhui; Zhang, Lei; Luo, Peng; Jiang, Xiaofan (Frontiers in Neurology, 2020)
Background: Cerebral cavernous malformations presenting with seizures can be treated with neurosurgery or radiosurgery, but the ideal treatment remains unclear. Currently, there is no adequate randomized controlled trial comparing surgical treatment and radiotherapy for epileptogenic CCMs. Therefore, we conducted a systematic review and meta-analysis of available data from published literature to compare the efficacy and safety of neurosurgery and radiosurgery for epileptogenic CCMs. Methods: We performed a comprehensive search of the Ovid MEDLINE, Web of Science, PubMed, China Biological Medicine and China National Knowledge Infrastructure databases for studies published between January 1994 and October 2019. The search terms were as follows: “epilepsy,” “seizures,” “brain cavernous hemangioma,” “cerebral cavernous malformation,” “cerebral cavernous hemangioma,” “hemangioma, cavernous, central nervous system.” Two researchers independently extracted the data and reviewed all the articles. We compared the advantages and disadvantages of the two treatments. Results: A total of 45 studies were included in our analysis. Overall, the seizure control rate was 79% (95% CI: 75-83%) for neurosurgery and 49% (95% CI: 38-59%) for radiosurgery. In the neurosurgery studies, 4.4 percent of patients experienced permanent morbidity, while no patients in the radiotherapy studies had permanent morbidity. In addition, the results of subgroup analysis showed that ethnicity, CCMs location and average lesion number are likely significant factors influencing the seizure outcome following treatment. Conclusions: The epilepsy control rate after neurosurgery was higher than that after radiosurgery, but neurosurgery also had a relatively higher rate of permanent morbidity.